Problematic issues of the legal regulation of local self-government officials’ remuneration - V. S. Govorov (Bulletin of Kharkiv National University of Internal Affairs)
The article draws attention to the fact that the current legislation on local self-government and service in local self-government bodies contains a number of problematic issues in terms of regulation of remuneration of officials. It is emphasized that this significantly reduces the effectiveness and reliability of material and financial guarantees for persons performing the tasks and functions of local self-government in positions in its bodies. Due to the low level of regulatory and legal control, the institution of salary does not fully perform the functions it is supposed to perform.